Teorija in zgodovina slovenske dramatike in gledališča - Pezdirc-Bartol, Mateja (Slavistična revija, 2013)
This article describes the processes in Slovene literary and drama studies that during the course of the twentieth century led to a crisis involving changes in the concept of theatricality and texts' performance dimensions, and the introduction of visual and spatial forms that were simultaneously employed in staging practices. These were incorporated into theory, which developed a compendium of scholarly definitions and terms. We have included comprehensive historical and theoretical representations of the evolution of post-WW II Slovene drama (by Denis Poniž, Silvija Borovnik, Janko Kos, Lado Kralj, and Malina Schmidt Snoj), along with studies of the relations between drama and the theater (by Tomaž Toporišič, Mateja Pezdirc Bartol, Blaž Lukan, and others).
Keywords: history of literature; literarna zgodovina; literary history; performance theory; Slovene drama; Slovene literature; Slovene theatre; slovenska dramatika; slovenska književnost; slovensko gledališče; teorija uprizarjanja